Analysis of water and energy conservation alternatives in Bangkok water supply system, Thailand - Kanchanapun Anusart; Babel, Mukand Singh; Perret, Sylvain Roger; Sutat Weesakul; Visvanathan, C.; Royal Thai Government Fellowship (Pathum Thani : Asian Institute of Technology, 2012)
Water is used to produce energy and energy is also needed to produce water and hence they are closely linked. Ever increasing demand of water and energy requires use to find ways to conserve these resources. This study aims to evaluate the current energy us in water supply system of Metropolitan Waterworks Authority (MWA) and analyzes several alternatives to conserve water and energy. A pilot area, DMA 15-03-02, has been selected for the purpose. A field measurements and survey (216 respondents) was conducted to obtain data for hydraulic modeling and household level energy use respectively in the pilot area. Five alternatives considered in the study are: Alternative 1 (decreasing service pressure), Alternative 2 (decreasing base demand), Alternative 3 (decreasing service pressure using hydro turbine generator) Alternative 4 (increasing service pressure) and Alternative 5 (increasing service pressure with pressure reducing valve, PRV). The secondary data of water production and energy consumption of MWA has been collected. The energy use in each stage of MWA is as follow: raw water intake 0.0097 (4%), water treatment 0.0469 (20%), water transmission 0.0961 (41%) and water distribution 0.0811 (35%). The energy use in the pilot area is estimated to be 0.1765 kWh/m3 by MWA and 0.5 kWh/m3 by customer, respectively. Decreasing in current service pressure indicates that water can be conserved while increasing the supply pressure would affect reduce energy use. Using hydro turbine can reduce pressure and also generate the electricity which can be used for another purpose. Moreover, PRV installation can help reducing leakage 20-25% in case of high pressure. Further, the analysis suggests that increasing pressure up to 18m with PRV can reduce total energy use by 32% (from 0.6765 to 0.4613 kWh/m3) as it will reduce the use of pumps by customer up to 95%.Further, the financial and economic cost-benefit analysis has been calculated in order to evaluate the alternative of water and energy conservation. Decreasing in service pressure is profitable for utility but not for customer due to the pump installation in household. While, some of pressure increasing alternative gives more profit for economic value although it is not for utility financial. This is because the capital cost of pump installation for customers is very high. Therefore, when people are not using pump, the benefit is much more than the cost of water leakage from MWA. Further, the analysis shows that increasing pressure up to 18m with PRV can give the most benefit considering the economic NPV for whole system
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering and Management
Thesis (M. Eng.) - Asian Institute of Technology, 2012
Keywords: Energy conservation -- Thailand -- Bangkok; Water conservation -- Thailand -- Bangkok